Quantitative analysis of relative volume of low apparent diffusion coefficient value can predict neurologic outcome after cardiac arrest. (May 2018) - Moon, Hyung Ki; Jang, Jinhee; Park, Kyu Nam; Kim, Soo Hyun; Lee, Byung Kook; Oh, Sang Hoon; Jeung, Kyung Woon; Choi, Seung Pill; Cho, In Soo; Youn, Chun Song
Abstract: Introduction: Predicting neurologic outcomes after cardiac arrest (CA) is challenging. This study tested the hypothesis that a quantitative analysis of diffusion weighted imaging (DWI) using the FMRIB Software Library (FSL) can predict neurologic outcomes after CA and can clarify the optimal apparent diffusion coefficient (ADC) thresholds for predicting poor neurologic outcomes. Methods: Out-of-hospital CA patients treated with targeted temperature management (TTM) who underwent DWI were included in this study. Voxel-based analysis was performed to calculate the mean ADC value. ADC thresholds (750, 700, 650, 600, 550, 500, 450 and 400) and brain volumes below each threshold were also analyzed for their correlation with outcomes. The patients were divided into early (within 48 h after return of spontaneous circulation (ROSC)) and late group (between 48 h and 7 days after ROSC) according to the DWI scan time. The primary outcome was a poor neurologic outcome at 6 months after CA, defined as a cerebral performance category (CPC) of 3–5. Results: One hundred ten DWIs were analyzed. The mean ADC values were 789.0 (761.5–826.5) × 10 −6 mm 2 /s for the good neurologic outcome group and 715.2 (663.1–778.4) × 10 −6 mm 2 /s for the poor neurologic outcome group (p < 0.001). All the ADC thresholds could differentiate patients with good versus poor outcomes. The ADC threshold of 400 × 10 −6 mm 2 /s had the highest odds ratio (4.648 in the early group and 11.283 in the late group) after adjusting for initial rhythm and anoxic time. To achieve 100% specificity using an ADC threshold of 400 × 10 −6 mm 2 /s, the sensitivity was 64% (cutoff value; >2.5% ADC threshold of 400 × 10 −6 mm 2 /s) in the early group and 79.2% (cutoff value; >1.66% ADC threshold of 400 × 10 −6 mm 2 /s) in the late group. Conclusions: Voxel-based analysis using FSL software can predict neurologic outcomes after CA. The ADC threshold of 400 × 10 −6 mm 2 /s had the highest OR for predicting a poor neurologic outcome.